Study on simulation effect of physical and chemical characteristics of sausage by sausage model system - Ji, Lili; Zhou, Chunyan; Zhou, Yanan; Nie, Qing; Luo, Yi; Yang, Rui; Wang, Shu; Ning, Jiawen; Zhang, Jiamin; Zhang, Ying (Frontiers in Nutrition, 2024)
Introduction The incorporation of Staphylococcus xylosus in sausage production is hypothesized to affect various physicochemical properties and flavor profiles of sausages. This study aimed to evaluate the simulation of these features in a sausage model and establish its applicability for in vitro studies. Methods Both a control and an experimental model, inclusive of Staphylococcus xylosus, were assessed for changes in physicochemical indexes (pH and water activity, Aw) and the concentration of flavoring components (esters and aldehydes). Thiobarbituric acid reactive substances (TBARS) values were also measured to evaluate lipid oxidation. Results The introduction of Staphylococcus xylosus resulted in no significant changes in pH and Aw between the sausage and the model. However, there was a considerable increase in the content of volatile flavor compounds, specifically esters and aldehydes, in the experimental groups compared to the control. Additionally, the TBARS values in experimental groups were significantly lower than those in the control group at the end of the testing period. Discussion The findings indicate that Staphylococcus xylosus plays a critical role in enhancing the flavor profile of sausages through the increased synthesis of volatile compounds and inhibiting fat oxidation. The sausage model effectively simulated the physicochemical and flavor index responses, demonstrating its potential utility for further in vitro research on sausage fermentation and preservation techniques.